Power Relations in Kamila Andini's Kretek Girl Film Series: An Analysis of Michel Foucault's Critical Discourse - Dewanto, Berlian Rahmah; Santoso, Hudi; Saleh, Amiruddin; Pranata, Rici Triharpin; Manisya, Nabhila; Maharani, Khalila Zahra (Golden Ratio of Data in Summary, 2025)
This research examines power relations in Kamila Andini's Gadis Kretek series using a Critical Discourse Analysis approach grounded in Michel Foucault's theory. Set in the kretek industry in Indonesia, the series explores themes of family conflict, business competition, and the search for identity through a cultural lens. This study investigates how power operates through discourse, discipline, and social control as reflected in the relationships between characters, which aligns with Foucault's theory. Discourses on tradition, gender, and national identity are analyzed as tools for normalizing and reinforcing dominance, particularly in maintaining hierarchies within the family business. The analysis focuses on specific scenes that highlight the stigmatization of thought, control of the body, and resistance to existing power structures. The findings reveal that the series portrays power not only as physical domination but also as control over the mind and body, deeply embedded in cultural practices and family relationships. This study offers a deeper understanding of how media represents power relations within Indonesia's social structure while emphasizing the symbolic significance of kretek as a representation of national identity.